Exploring Negative Online Interactions on X and Their Psychological Impact on Malaysian Gamers: A Qualitative Perspective - Balan, Dakshayani Siva; Mallanhanse, Armeetaa Kaur (Journal of Cultural Analysis and Social Change, 2025)
The rapid expansion of online gaming has created spaces for social connection while simultaneously fostering toxic behaviors that undermine players’ psychological well-being. Despite growing global concern, limited research has examined these experiences within non-Western cultural contexts. This study aimed (1) to explore Malaysian gamers’ experiences with negative online interactions on the platform X and (2) to examine how these interactions influence their mental well-being and coping strategies. Employing a qualitative phenomenological design, six Malaysian gamers aged 20 to 25 were recruited through purposive sampling and participated in semi-structured interviews. Data were analyzed thematically using NVivo. Findings revealed three main themes describing negative online experiences: toxicity and hostility in online interactions, harassment and targeted attacks, and structural and social dynamics of negativity, including the role of anonymity and misinformation. These interactions often led to emotional distress, such as stress, anxiety, and reduced self-esteem, and fostered long-term effects including social withdrawal and diminished trust in online communities. Nevertheless, participants demonstrated resilience through coping strategies such as detachment and avoidance, seeking supportive communities, and emotional regulation. The results highlight the dual nature of online gaming spaces as both supportive and psychologically taxing. Culturally, the findings suggest that Malaysia’s collectivistic values shape how toxicity is expressed and managed, emphasizing conformity and group harmony. This study underscores the importance of culturally grounded digital literacy programs, empathy-based interventions, and improved platform moderation to foster healthier online environments.